The Effectiveness of Ghorib Learning through Microsoft Teams E-Learning Platform in Indonesia - Syafi'i, Imam (Academia Publication, 2025)
This study aims to assess the success rate of learning Ghoroibul Qur'an through the Microsoft Teams e-learning platform for students of the Islamic Education Study Program at the Open University. The research method applied is mixed methods that integrates quantitative and qualitative approaches. Quantitative data were collected through questionnaires filled out by students, while qualitative data were collected from in-depth interviews and observations, in-depth interviews with students and lecturers. The results showed that e-learning in Ghoroibul Qur'an course can improve students' understanding Of Imalah, Isymam, Sakta, Tashil And correct pronunciation. Although there are some challenges, such as the lack of direct interaction between students and teachers, students who actively use digital learning technology tend to have better results, on the other hand, when learning to listen to the reading of students who have weak signals, the teacher is not fully able to correct due to the lack of clarity of the reading. In addition, this study identified the importance of applying blended learning methods to improve the effectiveness of learning Ghoroibul Qur'an. The findings are expected to contribute to designing more effective learning strategies in the digital era, especially in Islamic Religious Education at the University of Terbuka (UT) Indonesia.